Airborne Staphylococcus aureus in different environments—a review - Kozajda, Anna (Environ Sci Pollut Res Int, 2019)
The aim of the literature review was to describe the environments where the presence of airborne Staphylococcus aureus was confirmed and to catalogue the most often used methods and conditions of bioaerosol sampling to identify the bacteria. The basis for searching of studies on S. aureus in the bioaerosol in different environments was PubMed database resources from the years 1990–2019 (May). The review included studies which were carried on in selected environments: hospitals and other health care facilities, large-scale animal breeding, wastewater treatment plants, residential areas, educational institutions, and other public places. The highest concentrations and genetic diversity of identified S. aureus strains, including MRSA (methicillin-resistant S. aureus), have been shown in large-scale animal breeding. The role of the airborne transmission in dissemination of infection caused by these pathogens is empirically confirmed in environmental studies. Commonly available, well-described, and relatively inexpensive methods of sampling, identification, and subtyping guarantee a high reliability of results and allow to obtain fast and verifiable outcomes in environmental studies on air transmission routes of S. aureus strains.